Principles of engineering manufacture - Black, Stewart C. 1930-
The third edition of this text, formerly known as Principles of Engineering Production, has been thoroughly revised and updated and continues to provide students with a comprehensive overview of the technical considerations for the entire manufacturing process. In keeping with the developments in manufacturing technology, this new edition reflects the major advances in recent years, in particular, looking at the transition to computer controlled machinery and the developments in computer applications. Beginning with specification and standardisation, it analyses the key aspects of the manufact.